2017
DOI: 10.12692/ijb/11.1.68-74
|View full text |Cite
|
Sign up to set email alerts
|

Major diseases of cashew (Anacardium Occidentale L.) Caused by fungi and their control in Odisha, India

Abstract: Cashew is an important cash crop in India but the incidence of diseases incur considerable losses in cashew plantations leading to reduction both in terms of quality and quantity. The present investigation was to study the fungi associated with cashew plant in Odisha in view of the warm and humid climate. Isolation, identification, pathogenicity test and nutritional study of the test fungi as well as the control was undertaken in vitro. The result of the study revealed that seven species of fungi namely Pestal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The results of the pathogenicity test are in agreement with those of Wonni et al (2017) who after inoculation of young cashew trees containing 6-8 leaves by P. heterocornis, obtained symptoms similar to those of pestalotia 2-3 weeks later In addition, Uaciquete (2013) obtained similar results with the anthracnose pathogen (Colletotrichum gloeosporioides) in Mozambique on young leaves detached from the cashew tree. Khatoon et al (2017) in India and Nakpalo et al (2017) showed that the isolates were pathogenic on young plants aged six to seven months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the pathogenicity test are in agreement with those of Wonni et al (2017) who after inoculation of young cashew trees containing 6-8 leaves by P. heterocornis, obtained symptoms similar to those of pestalotia 2-3 weeks later In addition, Uaciquete (2013) obtained similar results with the anthracnose pathogen (Colletotrichum gloeosporioides) in Mozambique on young leaves detached from the cashew tree. Khatoon et al (2017) in India and Nakpalo et al (2017) showed that the isolates were pathogenic on young plants aged six to seven months.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found by different authors. Anthracnose (Colletotrichum gloeosporioides), pestalotia leaf spot (Pestalotia heterocornis) and powdery mildew (Oïdium anacardii) have also identified among major diseases attacking cashew trees in Tanzania (NARI, 2009;Msoka, 2017), in Bénin (Afouda et al, 2013), in India (Khatoon et al, 2017) and Kenya (Menge & Marthamakobe, 2016). Drying of the buds (Phomopsus anacardii) has also been reported in Mozambique (Uaciquete, 2013), in Ivory Coast (Nakpalo et al, 2017) and Burkina Faso (Wonni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work identified red rust due to C. virescens in soursop, safou, guava and cocoa in the surveyed sites. Several authors have identified red rust due to C. virescens in other species [18,19]. The presence of the alga is favoured by average monthly temperatures and rainfall of 23 °C and 127 mm respectively [15].…”
Section: Discussionmentioning
confidence: 99%
“…Today several diseases have been shown to be severe enough to cause cashew trees to suffer major losses. This farm crop is reported to be attacked by several fungi, which reduces productivity [35]. Numerous biotic and abiotic restrictions are a hazard to cashew, causing severe output losses.…”
Section: Introductionmentioning
confidence: 99%